Optimization of Functional Properties of Cocoyoghurt through Fortification with Moringa Leaf Extract (Moringa oleifera): Antioxidant Activity and Organoleptic Characteristics - Sintyadewi, Putu Rima; Widnyani, Ida Ayu Putu Ary; Putra, Anak Agung Ngurah Dwi Ariesta Wijaya; Wulansari, Nadya Treesna (Jurnal Pijar Mipa, 2025)
Yogurt is a fermented milk product known as a functional food. Food diversification efforts by finding alternative yogurt raw materials to replace animal milk are necessary to provide products for people who want alternative non-dairy yogurt products. One of the plant-based milks that has a nutritional content similar to animal milk is coconut (Cocos nucifera). Moringa leaves (Moringa oleifera) are reported to contain antioxidant compounds and have therapeutic benefits, making them potentially suitable for use as a fortifier in cocoyogurt functional drinks. The purpose of this study was to obtain the most appropriate formula for adding moringa leaf extract to produce cocoyogurt products that are high in antioxidants and have physicochemical and organoleptic properties that are acceptable to consumers. The design used in this study was a completely randomized design (CRD) with 4 treatments, namely: P0 = without the addition of moringa leaf extract; P1 = moringa leaf extract 1 g/L; P2 = moringa leaf extract 2 g/L; and P3 = moringa leaf extract 3 g/L. The data obtained were analyzed using the Analysis of Variance (ANOVA) statistical method and continued with Duncan's Multiple Range Test if there was a significant difference (P ≤ 0.05) between treatments. Based on the results of the study, it is known that the addition of moringa leaf extract to coconut milk yogurt produces cocoyoghurt with a low acidity (pH) (4.5-44.3), which is in accordance with the SNI standard (2981-2009) for yogurt quality. Overall, the best treatment in cocoyoghurt was the addition of 3 g/L of moringa leaf extract with an IC50 value of 148.33 µg/ml, with free radical inhibitory activity in the moderate category, and the sensory properties of taste, aroma, color, and texture showed the most preferred values ​​by the panellists. These findings have broader implications for functional food innovation, particularly in developing plant-based, nutrient-enriched products that cater to lactose-intolerant populations and health-conscious consumers seeking natural sources of antioxidants.